Linking ecomechanical models and functional traits to understand phenotypic diversity. (September 2021) - Higham, Timothy E.; Ferry, Lara A.; Schmitz, Lars; Irschick, Duncan J.; Starko, Samuel; Anderson, Philip S.L.; Bergmann, Philip J.; Jamniczky, Heather A.; Monteiro, Leandro R.; Navon, Dina; Messier, Julie; Carrington, Emily; et al.
Abstract : Physical principles and laws determine the set of possible organismal phenotypes. Constraints arising from development, the environment, and evolutionary history then yield workable, integrated phenotypes. We propose a theoretical and practical framework that considers the role of changing environments. This 'ecomechanical approach' integrates functional organismal traits with the ecological variables. This approach informs our ability to predict species shifts in survival and distribution and provides critical insights into phenotypic diversity. We outline how to use the ecomechanical paradigm using drag-induced bending in trees as an example. Our approach can be incorporated into existing research and help build interdisciplinary bridges. Finally, we identify key factors needed for mass data collection, analysis, and the dissemination of models relevant to this framework. Highlights: All organisms must comply with physical laws, which place rigid or hard constraints on survival and reproduction. Ecomechanics is the expression of that interplay, and assumes a central role when considering organismal development, ecology, and evolution. How organisms will respond to changes in the environment, such as human-mediated climate change, will depend strongly on ecomechanics. Functional traits are commonly used to investigate the consequences of ecological variation. Ecomechanical models that incorporate functional traits and environmental variables are key to deciphering the rules of life and expand upon functional trait studies. The use of the ecomechanical framework is illustrated using multiple examples (e.g., wind-induced bending mechanics in trees and gecko adhesion in the real world). We emphasize safety factors as a key metric when assessing the evolution of form and performance. Biologists can apply our framework to many other systems. We offer suggestions for constructing and tailoring the data pipeline for future ecomechanical models to enhance their availability and utility for various disciplines.